Breaking the promise: transitional justice between tactical concession and legacies of authoritarian regime in Indonesia - Wahyuningroem, Sri Lestari (International journal of transitional justice, 2022)
For more than two decades after the authoritarian regime ended in Indonesia, transitional justice remains an unfinished agenda in the new democracy. In every government leadership, transitional justice issues re-emerged and later vanished or failed at implementation. Post-Suharto’s presidents have always succeeded in getting support by including the transitional justice agenda in their campaigns and the early days of their leadership. Yet, none resulted in truth and justice as promised. Transitional justice is used as a tactical concession and has proven successful in gaining support for political winnings; it provides the avenue for one to gain political legitimacy and support, as it promises a distance from the previous regime. However, adopting transitional justice measures did not in any way lead to a change in state behaviour, let alone to institutionalizing and internalizing justice and accountability. I argue in this article that authoritarian regime factors contributed to the impunity for perpetrators and the lack of truth and acknowledgement about past abuses in Indonesia today.